2010
DOI: 10.1016/j.nuclphysb.2009.08.014
|View full text |Cite
|
Sign up to set email alerts
|

The square-lattice quantum liquid of charge c fermions and spin-neutral two-spinon s1 fermions

Abstract: The momentum bands, energy dispersions, and velocities of the charge c fermions and spin-neutral two-spinon s1 fermions of a square-lattice quantum liquid referring to the Hubbard model on such a lattice of edge length L in the one-and two-electron subspace are studied. The model involves the effective nearest-neighbor integral t and on-site repulsion U and can be experimentally realized in systems of correlated ultra-cold fermionic atoms on an optical lattice and thus our results are of interest for such syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
52
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(55 citation statements)
references
References 76 publications
(419 reference statements)
3
52
0
Order By: Relevance
“…[2] first showed sufficient details of the spin-wave spectrum to demonstrate that a simple nearest-neighbor Heisenberg model must be supplemented by a number of additional terms, including ring exchanges. These terms arise naturally out of a single band Hubbard model with finite U/t, and several detailed studies showed that the spin-wave data in the available energy window could be successfully described by the Hubbard model using a somewhat smaller value of U/t ∼ 6 − 8 than originally thought appropriate [2][3][4][5]. However, part of the spectral weight was deduced to be outside the energy window.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[2] first showed sufficient details of the spin-wave spectrum to demonstrate that a simple nearest-neighbor Heisenberg model must be supplemented by a number of additional terms, including ring exchanges. These terms arise naturally out of a single band Hubbard model with finite U/t, and several detailed studies showed that the spin-wave data in the available energy window could be successfully described by the Hubbard model using a somewhat smaller value of U/t ∼ 6 − 8 than originally thought appropriate [2][3][4][5]. However, part of the spectral weight was deduced to be outside the energy window.…”
mentioning
confidence: 99%
“…This raises the important question of whether the more detailed results can still be described in terms of a simple Hubbard model. Here we address this question using a combination of a number of theoretical and numerical approaches, including, in addition to standard treatments, a new spinon approach for the spin excitations [5,7] and density matrix renormalization group (DMRG) calculations for Hubbard cylinders [8][9][10]. We show that the Hubbard model does describe the new neutron scattering results.…”
mentioning
confidence: 99%
See 3 more Smart Citations